Reversible data hiding method by extending reduced difference expansion - Zainal Syahlan; Tohari Ahmad (International Journal of Advances in Intelligent Informatics, 2019)
To keep hiding secret data in multimedia files, such as video, audio, and image considers essential for information security. Image, for instance, as the media aids data insertion securely. The use of insertion technique must ensure a reliable process on retaining data quality and capacity. However, a trade-off between the resulted image quality and the embedded payload capacity after the embedding process often occurs. Therefore, this research aims at extending the existing method of integrating confidential messages using the Reduced Difference Expansion (RDE), transform into a medical image by changing the base point, block size, and recalculating of difference. The results display that the proposed method enhances the quality of the stego image and capacity of the hidden message.